Effect of endurance training on copper, zinc, iron and magnesium status - Rakhra, G.; Masih, D.; Vats, A.; Verma, S. K.; Singh, V. K.; Kirar, V.; Singh, S. N. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Physical activity related energy expenditure, environmental stresses, body composition, dietary intake, etc., are key factors influencing the nutritional requirements of minerals. The present study was designed to study the nutritional status of metals with respect to extensive endurance training. METHODS: The participants of the study were navy sailors (N.=37, mean age±SD: 25.2±4.8 y) undergoing one month of endurance training. Nutritional status was assessed by determining their body composition using bioelectrical impedance (BIA), food intake and urinary excretion levels. Fasting blood samples were taken to separate plasma and red blood cells for analysis of copper, zinc, magnesium and iron and certain metal dependent enzymatic biomarkers. RESULTS: Endurance training significantly decreased the plasma levels of copper (P<0.01), zinc and iron (P<0.05) while in erythrocytes a significant (P<0.001) decrease was observed only for Mg and Zn. There was a concomitant increase (P<0.05) in urinary Zn excretion. In addition, the concentrations of certain metal dependent enzymatic biomarkers like RBC metallothionein (P<0.05) and carbonic anhydrase (P<0.01) (Zn biomarker), plasma ferritin (Fe biomarker) (P<0.001) and RBC Mg ATPase (Mg biomarker) (P<0.05) decreased after physical activity. CONCLUSIONS: The findings of the present study suggested the increased requirements of these minerals during physical activity.